THE EFFECT OF ORGANIZATIONAL CLIMATE, SELF-EFFICACY AND JOB SATISFACTION ON LECTURERS PROFESSIONAL COMMITMENT AT PAKUAN UNIVERSITY - Sunardi, Oding (JERAM, 2017)
ABSTRACT   Professional commitment of Pakuan University lecturer plays a crucial role in achieving the student learning outcomes. Based on pre-research survey of Pakuan University Report on 2015 professional commitment among lecturer is still low and not satisfactory. The objective of this research is to investigate whether there exists any direct positive effect of organizational climate, self-efficacy and job satisfaction towards professional commitment at University of Pakuan. A total of 189 from 324 university lecturer were sampled to collect data which was then analyzed using path analysis quantitative method. The result shows that there exists a direct positive effect of organizational climate towards professional commitment, self-efficacy toward professional commitment, job satisfaction towards professional commitment, organizational climate job satisfaction, self-efficacy toward job satisfaction, and organizational climate towards self-efficacy. Keywords: organizational climate, self-efficacy, job satisfaction, professional commitment